Expression and prognostic value of PRDX family in colon adenocarcinoma by integrating comprehensive analysis and in vitro and in vivo validation - Zhou, He; Li, Lifa; Chen, Jia; Hou, Songlin; Zhou, Tong; Xiong, Yongfu (Frontiers in Oncology, 2023)
The peroxiredoxin family, a crucial regulator of redox reactions, is strongly associated with various tumorigenesis. However, the role of peroxiredoxin4 (PRDX4) in colon adenocarcinoma (COAD) remains poorly understood. Multicenter databases, including GEPIA, HPA, UALCAN, cBioPortal, cancerSEA, STRING, CCLE, and LinkedOmics, comprehensively analyzed transcriptional expression, prognostic value, genetic alterations, signaling pathways, and associated genes of the PRDXs in COAD patients. Colony formation, transwell, flow cytometry, sphere formation, and xenograft assays were performed to validate further in vitro and in vivo. Members of the PRDX family were differentially expressed in COAD, with each member showing varying degrees of genetic alterations. Intriguingly, only PRDX4 significantly correlated with COAD prognosis and stage. The single-cell sequencing suggested that PRDX4 is positively correlated with proliferation, apoptosis, and invasion, whereas negatively correlated with stemness. Moreover, PRDX4 involved in a series of critical biological processes, such as cell growth. Furthermore, in vivo and in vitro analyses indicated that knocking down PRDX4 inhibits the proliferation and invasion of HCT116 cells while promoting apoptosis and stemness. In conclusion, we identified PRDX4 expression as a novel potential prognostic marker in COAD.